Analysis of Acoustic Cavitation Surge in a Rocket Engine Turbopump. (12th January 2011) - Nanri, Hideaki; Kannan, Hiroki; Tani, Naoki; Yoshida, Yoshiki
Abstract : In a liquid rocket engine, cavitation in an inducer of a turbopump sometimes causes instability phenomena when the inducer is operated at low inlet pressure. Cavitation surge (auto-oscillation), one such instability phenomenon, has been discussed mainly based on an inertia model assuming incompressible flow. When this model is used, the frequency of the cavitation surge decreases continuously as the inlet pressure of the turbopump decreases. However, we obtained an interesting experimental result in which the frequency of cavitation surge varied discontinuously. Therefore, we employed one-dimensional analysis based on an acoustic model in which the fluid is assumed to be compressible. The analytical result qualitatively corresponded with the experimental result.